Study Skills and Test Taking Strategies for Coaching Medical Learners Based on Identified Areas of Struggle - Jeannette Guerrasio; Carmella Nogar; Matthew Rustici; Carol Lay; Janet Corral (Association of American Medical Colleges, 2017)
Introduction Learners in high-performing contexts such as medical school and residency are presumed to have appropriate study skills to be successful. However, for those learners in academic difficulty who are identified as having weak study skills and poor test taking skills, faculty need tools to use to lead these struggling learners to academic success. In coaching learners on study skills, we frequently found that the study skills that helped them get into medical school or residency were no longer sufficient to make them successful in their new program. Given that there are multiple study strategies available, faculty coaches need mechanisms to first tease out which skills are the issue and then provide targeted strategies specific to each learner. Methods In meeting with a faculty coach, learners are briefly interviewed, complete a self-assessment to explore all possible root weaknesses in their study skills, and then read strategic solutions and review with faculty how they may be implemented. This tool has been offered to 52 students, 76 residents, and 20 fellows and faculty between 2010 and 2015. Results One hundred forty-eight individuals participated in this innovation, with more than 91% of all individuals going on to pass the exam that they had either failed or, in the case of the in-training exam, scored below the 30th percentile on. Conclusion A self-assessment tool is key to individualized insight and action plans for improving study skills. Implementation must be supported with concurrent in-person coaching.